Pengaruh Current Ratio dan Working Capital Turnover terhadap Return on Equity pada PT Indocement Tunggal Prakarsa Tbk - Lia, Nur Awalia Sofiyanti; Muhammad Badar; Jaenab, Jaenab (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of Current Ratio and Working Capital Turnover on Return on Equity at PT Indocement Tunggal Prakarsa Tbk. Return on Equity (ROE) is a key indicator used to measure a company's efficiency in generating profits from shareholders' equity. The Current Ratio measures the company’s ability to meet its short-term obligations, while Working Capital Turnover reflects the company’s efficiency in utilizing working capital to generate revenue. This research uses a quantitative approach with descriptive and verification methods. Secondary data was obtained from the annual financial reports of PT Indocement Tunggal Prakarsa Tbk for a specified period. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results show that partially, the Current Ratio has a negative and insignificant effect on Return on Equity. Meanwhile, Working Capital Turnover has a positive and significant effect on Return on Equity. Simultaneously, both independent variables have a significant effect on Return on Equity. These findings indicate that effective working capital management contributes more to improving company profitability than liquidity alone. Therefore, the company is advised to continue improving the efficiency of working capital utilization to provide added value to shareholders through increased return on equity.